2021
DOI: 10.1002/14651858.cd006386.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for the treatment of oral cavity and oropharyngeal cancer: chemotherapy

Abstract: BackgroundOral cavity and oropharyngeal cancers are frequently described as part of a group of oral cancers or head and neck cancer. Treatment of oral cavity cancer is generally surgery followed by radiotherapy, whereas oropharyngeal cancers, which are more likely to be advanced at the time of diagnosis, are managed with radiotherapy or chemoradiation. Surgery for oral cancers can be disfiguring and both surgery and radiotherapy have significant functional side effects, notably impaired ability to eat, drink a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 406 publications
0
26
0
1
Order By: Relevance
“…30 Side effects such as systemic chemotherapy and multidrug resistance are the most frequently encountered issues in cancer chemotherapy. 170 It remains a huge challenge to improve therapeutic efficacy as well as minimize the adverse effect. Inspired by this, Chen et al developed cancer cell membranes (CM)@cobalt-ferrocene metal-organic framework (Co-Fc)@ hydroxychloroquine (HCQ) (CM@Co-Fc@HCQ) for effective ablation of OSCC (Fig.…”
Section: Neoantigen-based Chemotherapy/chemodynamic Therapy (Cdt)mentioning
confidence: 99%
“…30 Side effects such as systemic chemotherapy and multidrug resistance are the most frequently encountered issues in cancer chemotherapy. 170 It remains a huge challenge to improve therapeutic efficacy as well as minimize the adverse effect. Inspired by this, Chen et al developed cancer cell membranes (CM)@cobalt-ferrocene metal-organic framework (Co-Fc)@ hydroxychloroquine (HCQ) (CM@Co-Fc@HCQ) for effective ablation of OSCC (Fig.…”
Section: Neoantigen-based Chemotherapy/chemodynamic Therapy (Cdt)mentioning
confidence: 99%
“…The following research questions were used to guide the conduct of the present study: (1) What kinds of non-PROs and PROs are reported in RCTs involving the treatment of head and neck neoplasms? (2) Are there any temporal trends in the reporting of PROs in RCTs involving the treatment of head and neck neoplasms?…”
Section: Research Questionmentioning
confidence: 99%
“…In contrast, relying only on outcomes from the perspective of the researcher provides a limited view of the potential impact of therapies. For example, Parmar et al 1 is a systematic review of compiled evidence on the effect of chemotherapy for treating oral and oropharyngeal cancer. However, it only reports endpoints for survival and locoregional control.…”
Section: Introductionmentioning
confidence: 99%
“…Author details 1 4 Department of Oral and Maxillofacial Surgery, School and Hospital of Stomatology, Wuhan University, Wuhan, Hubei, 430079, China. 5 Authors contributing equally to this work. 6 Lead contact *Corresponding Author: Hongyu Yang, E-mail: hyyang192@hotmail.com; Gang Chen, E-mail: geraldchan@whu.edu.cn…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…However, some tumors are highly aggressive and resistant to chemotherapy and are often associated with a poor prognosis [4]. Despite the wide use of cisplatin-based chemotherapy, the overall cure rate of patients with R/M OSCC remains very low, with an estimated 5-year survival rate of < 50% [5].…”
Section: Introductionmentioning
confidence: 99%